SPIRITUAL DIMENSIONS OF CREATIVITY: A PHILOSOPHICAL INQUIRY INTO MULTIMODAL AFFECTIVE COMPUTING AND EMOTIONAL GUIDANCE IN ART EDUCATION - Zhu, Hongjng (European journal for philosophy of religion, 2025)
The cultivation of creativity in art education is not merely a cognitive or technical process but also a deeply philosophical and spiritual endeavor. Emotions, as integral components of human consciousness, play a crucial role in shaping artistic inspiration, imaginative expression, and the transcendent experience of creativity. This study explores the role of multimodal affective computing in emotional guidance within art education, integrating philosophical and theological perspectives on creativity, inspiration, and the human experience of artistic expression. By analyzing the interaction between emotions, cognition, and creativity, this research examines how computational technologies can facilitate a more profound engagement with artistic and spiritual dimensions in education. The study employs a personalized art teaching model based on multimodal affective computing, measuring students’ emotional intensity in real-time through multimodal data collection in fine arts classrooms. A comparative teaching experiment was conducted with fine arts students at a university, assessing their creativity development before and after the intervention. Through independent sample tests and regression analysis, the findings reveal that multimodal emotions have a significant positive impact on creativity at the 1% level. The emotional intensity thresholds for optimal artistic engagement were identified at 0.25 (positive) and -0.25 (negative), with students’ emotional distributions mostly ranging between [-0.2, 0.1]. After implementing the affective computing-supported teaching model, students in the experimental group demonstrated a 13.94-point increase in creativity scores, which was 17.67% higher than those in the control group. Beyond technological efficiency, this study reflects on the philosophical and spiritual implications of emotional engagement in artistic creation. Drawing on religious and metaphysical perspectives, it considers the role of emotions in fostering divine inspiration, self-transcendence, and artistic enlightenment. By enabling art educators to better understand students’ emotional states, multimodal affective computing can enhance emotional guidance in teaching, leading not only to improved artistic creativity but also to a deeper connection between artistic practice, spiritual growth, and philosophical reflection. Future research should explore how computational tools can further support the integration of spiritual and artistic experiences, enriching both pedagogical practice and the metaphysical dimensions of creativity.